The pecularities of future military pilots aviation language teaching as a language for special purposes - Sopova A. S., Nikolaeva N. I. (Interactive science, 2016)
the article considers the issues of military institute cadets teaching of Aviation English language as a language for special purposes in the process of profession-oriented training. The authors emphasize the fact that analysys of typical professional and communicative situations, formation of professional and communicative competence, the skill of using speech formulas for realizing communication in the aviation sphere play the main role in the future military pilots training.
Keywords: английский язык; профессионально-коммуникативная компетентность; специальные цели; авиационный английский язык; военные летчики; военный вуз; профессионально-ориентированная подготовка; Aviation English language; English for special purposes (ESP); military institute; military pilots; professional and communicative competence; profession-oriented training